2012
DOI: 10.1155/2012/432752
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Muscle Stimulation: An Effective Form of Exercise and Early Mobilization to Preserve Muscle Strength in Critically Ill Patients

Abstract: Purpose. This is a secondary analysis of previously published data to investigate the effects of electrical muscle stimulation (EMS) on strength of various muscle groups in critically ill patients. Methods. One hundred forty-two consecutive patients, with APACHE II score ≥ 13, were randomly assigned to the EMS or the control group. EMS sessions were applied daily on vastus lateralis, vastus medialis, and peroneus longus of both lower extremities. Various muscle groups were evaluated with the Medical Research C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 33 publications
5
87
0
1
Order By: Relevance
“…One trial in 140 patients reported a decrease in incidence of ICUAW from 39.3 to 12.5%, accompanied by a shorter time to weaning in the intervention group (598). These data should be interpreted with caution, since significant differences for baseline characteristics, APACHE II, and certain comorbidities were present between groups in the subset of actually evaluated patients (357). Another RCT in COPD patients in the ICU found no incidence of ICUAW in EMS-treated patients.…”
Section: Electrical Muscle Stimulationmentioning
confidence: 99%
“…One trial in 140 patients reported a decrease in incidence of ICUAW from 39.3 to 12.5%, accompanied by a shorter time to weaning in the intervention group (598). These data should be interpreted with caution, since significant differences for baseline characteristics, APACHE II, and certain comorbidities were present between groups in the subset of actually evaluated patients (357). Another RCT in COPD patients in the ICU found no incidence of ICUAW in EMS-treated patients.…”
Section: Electrical Muscle Stimulationmentioning
confidence: 99%
“…This body of evidence can be said to be inadequate, in consideration of the low number of subjects in the electric muscle stimulation group and the associated risk of bias, in addition to the lack of a high‐quality systematic review or meta‐analysis at this time. Three single‐center RCTs examining whether muscle mass increases as a result of electrical muscle stimulation437, 438, 439 were identified and subjected to a meta‐analysis 440. Although subject muscle mass increased significantly, the total number of subjects in the electric muscle stimulation group was low (72 subjects) and the bias risk was high, and accordingly, this evidence may be considered to be of poor quality.…”
Section: Cq18: Icu‐acquired Weakness (Icu‐aw) and Post‐intensive Carementioning
confidence: 99%
“…This review included eight RCTs (15,(34)(35)(36)(37)(38)(39)(40) and one casecontrol study (41). Evaluation of EMS in the ICU is a rapidly growing area of research as evidenced by 40% of the reviewed studies being published within the past year (15,35,40).…”
Section: Study Characteristicsmentioning
confidence: 99%